Language Policy as a Focal Point in English-Medium International Schools - Clayton Lehman; Brett Welch (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
A language policy in an international school is a document that should state how language will be taught, learned, and used. In essence, a language policy can provide organization and cohesion for an international school as it works to deliver a curriculum to the students, and many students enrolled in international schools are English language learners (ELLs). This quantitative survey-based study aimed to investigate teacher adherence and knowledge of language policy in English-medium international schools. Also explored was the provision of professional development for working with ELLs and teacher self-efficacy when teaching ELLs in relation to language policy knowledge. Compared to previously reported data, key findings showed a rise in the percentage of teachers reporting their school had a language policy and a lower percentage of teachers reporting they were consistently following the policy. Additional findings were that less than half of the participants reported their school provided a medium or higher frequency of professional development for working with ELLs, and teachers who had knowledge of the language policy had higher self-efficacy levels when teaching ELLs than teachers who had no knowledge of a language policy.